Identification the Use of Goodcash Mobile Application as a Money Managing Tool of Goodism Inc.’s Customers - Cincin, Meiliane Stephanie; Iskandar, Budi Permadi (Journal of Business and Management, 2015)
Abstract. The consumption pattern of overspending might become one of the most common problems in the world including Indonesia. This could be happened because a person's consumption patterns are formed during youth age as youth are still looking for their own self-identity. Therefore they become less interested in saving money and their attitudes towards saving are more negative than earlier and later in life. Goodism Inc as an innovative start up company not only saw an opportunity from this problem by selling a product (since most brands are attracted to this kind of potential buyer), but they also try to bring solution to their target market with their product. The product they sell is wallet with a concept as a money manager, to complete their innovative idea, they created a mobile application called Goodcash to be a financial tracker. But they don’t have any proof that their mobile application runs as they want it to be, and the company don’t really know whether the cost they spent for Goodcash is worth every pennies or not. For that reason, the author as one of the co-founder of Goodism Inc wants to identify the use of Goodcash as a money manager tool of Goodism Inc’s customers. And at the end of the research the author found that this mobile application is not quite succesfull as the company wanted before.This unsuccessful reason is because the mobile application still needs some improvements that made the customers didn’t want to use this application. But strangely, some respondents is quite satisfy and didn’t think that the mobile application is bad but they just don’t have the awareness of doing financial management and admit that they were too lazy to do that. The habit of getting use to do financial management is also required to make this project successful. That is considered as Goodism Inc’s task to create that habit in the mind of their customers. In the end of the research, the company should work harder to increase their brand value through Goodcash.